Masculinity and Cultural Values in Folk Stories - Dedi Febriyanto; Yessi Fitriani; Puspa Indah Utami (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Folklore as part of local literature in Indonesia displays a variety of social realities. There are several social realities that are widely depicted in folklore related to gender, masculinity and cultural values. This study was conducted with the aim of theoretically describing aspects of masculinity and cultural values ​​in folklore. This study was carried out using a qualitative descriptive method with a literature study approach. Based on the study, it can be seen that folk tales as part of local literary works display various aspects of gender masculinity and cultural values. The gender aspects in question can include physical, functional, sexual, emotional, intellectual, interpersonal and other personal character aspects. As for cultural values, they include the cultural values ​​of the relationship with God, nature, oneself and fellow humans.